Boron–Nitrogen‐Doped Nanographenes: A Synthetic Tale from Borazine Precursors. Issue 29 (24th March 2020) - Dosso, Jacopo; Battisti, Tommaso; Ward, Benjamin D.; Demitri, Nicola; Hughes, Colan E.; Williams, P. Andrew; Harris, Kenneth D. M.; Bonifazi, Davide
Abstract: In this work, a comprehensive account of the authors' synthetic efforts to prepare borazino‐doped hexabenzocoronenes by using the Friedel–Crafts‐type electrophilic aromatic substitution is reported. Hexafluoro‐functionalized aryl borazines, bearing an ortho fluoride leaving group on each of the N‐ and B‐aryl rings, was shown to lead to cascade‐type electrophilic aromatic substitution events in the stepwise C−C bond formation, giving higher yields of borazinocoronenes than those obtained with borazine precursors bearing fluoride leaving groups at the ortho positions of the B‐aryl substituents. By using this pathway, an unprecedented boroxadizine‐doped PAH featuring a gulf‐type periphery could be isolated, and its structure proven by single‐crystal X‐ray diffraction analysis. Mechanistic studies on the stepwise Friedel–Crafts‐type cyclization suggest that the mechanism of the planarization reaction proceeds through extension of the π system. To appraise the doping effect of the boroxadizine unit on the optoelectronic properties of topology‐equivalent molecular graphenes, the all‐carbon and pyrylium PAH analogues, all featuring a gulf‐type periphery, were also prepared. As already shown for the borazino‐doped hexabenzocoronene, the replacement of the central benzene ring by its B3 N2 O congener widens the HOMO–LUMO gap and dramatically enhances the fluorescence quantum yield. Abstract : Nanographene doping : The preparation of borazino‐doped hexabenzocoronenes by using the Friedel–Crafts‐type electrophilic aromatic substitution is reported. Hexafluoro‐functionalized aryl borazines led to cascade‐type electrophilic aromatic substitution events in the stepwise C−C bond formation. A new boroxadizine‐doped PAH featuring a gulf‐type periphery was isolated. Mechanistic studies on the reaction and evaluation of the doping effect on the optoelectronic properties are also reported.